Therapy of chronic hepatitis C in people who inject drugs: focus on adherence - Frankova, Sona; Jandova, Zuzana; Jinochova, Gabriela; Kreidlova, Miluse; Merta, Dusan; Sperl, Jan (Harm reduction journal, 2021)
BACKGROUND: Intravenous drug use (IVDU) represents the major factor of HCV transmission, but the treatment uptake among people who inject drugs (PWID) remains low owing to a false presumption of low efficacy. The aim of our study was to assess treatment efficacy in PWID and factors determining adherence to therapy. METHODS: A total of 278 consecutive patients starting DAA (direct-acting antivirals) therapy were included, divided into two groups: individuals with a history of IVDU, PWID group (N = 101) and the control group (N = 177) without a history of IVDU. RESULTS: Sustained virological response 12 weeks after the end of therapy (SVR12) was achieved by 99/101 (98%) and 172/177 (98%) patients in the PWID and control group, respectively; in PWID group, two patients were lost to follow-up, and in the control group, four patients relapsed and one was lost to follow-up. PWID patients postponed appointments significantly more often, 29 (28.7%) in PWID versus 7 (4%) in the control group, p = 0.001. Thirteen of 101 (12.9%) and six of 177 (3.4%) patients in the PWID and in the control group, respectively, missed at least one visit (p < 0.01). However, postponing visits led to a lack of medication in only one PWID. In the PWID group, older age (p < 0.05; OR 1.07, 95% CI 1.00-1.20) and stable housing (p < 0.01; OR 9.70, 95% CI 2.10-56.20) were factors positively contributing to adherence. Contrarily, a stable job was a factor negatively influencing adherence (p < 0.05; OR 0.24, 95% CI 0.06-0.81). In the control group, none of the analyzed social and demographic factors had an impact on adherence to therapy. CONCLUSIONS: In PWID, treatment efficacy was excellent and was comparable with SVR of the control group. Stable housing and older age contributed to a better adherence to therapy.
Keywords: senioři; Aged; Antiviral Agents; chronická hepatitida C; hepatitida C; Adherence; Drug user; Hepatitis C; Treatment; Czech Republic; antivirové látky; Substance Abuse, Intravenous; setrvalá virologická odpověď; PWID; intravenózní abúzus drog; Sustained Virologic Response; Hepatitis C, Chronic; lidé; Humans; Pharmaceutical Preparations; léčivé přípravky